Relationship Between Visionary Leadership Of Principals And Teachers’ Performance Of Early Childhood Education Institutions In Purworejo Sub District Of Purworejo Regency, Central Java - Ulfa, Dama; Waluyo, Edi (Jurusan PGPAUD FIP UNNES, 2016)
The principals and the teachers are two main elements in the early childhood education institutions. The relationships between them are very important to hold good cooperation and to give the best services for the learners. The teachers are one of human resources in the educational institutions. The teachers’ performance plays important roles to gain organizational objectives. The problems on the teachers’ performance have to be concerned more, because a teacher’s figure is an important matter when we are talking about the educational world. The teachers are always related with educational components and system. They play the important roles in the education development, particularly those which are implemented formally in the school. They also determine the success of the learning participants.This research used correlation quantitative method. The population in this research was all the principals and teachers of the early childhood education institutions in Purworejo sub district covering 5 early childhood institutions consisting of 77 principals and teachers. The samples were taken using simple random sampling technique as many as 65 principals and teachers. The data collection was done using Likert scale. The assumption test used normality and linearity techniques. The results of Pearson correlation product moment showed that there was a positive and significant relationship between the visionary leadership of the principals and the teachers’ performance in Purworejo sub district of Purworejo regency. The value of correlation coefficient was 0,848 with the significance value of 0,000< 0,05. The stronger the visionary leadership of the principals, the better the teachers’ performance of the early childhood education institutions in Purworejo sub district of Purworejo regency.The final conclusion was there was a positive and significant relationship between the visionary leadership of the principals and the teachers’ performance of the early childhood education institutions in Purworejo sub district of Purworejo regency